On A Class of Real Quintic Moment Problem - Abdelaziz El Boukili; Amar Rhazi; Bouazza El Wahbi (IndoMS, 2023)
The present paper is centered on a class of real quintic moment problem. We state some conditions for the existence of a representative measure and we provide it explicitly. We also state some cases where no representative measure exists. Some numerical examples are presented to illustrate construction of the representative measure as well as to highlight the conflicts behind the irresolvability.